Analysis of Stock Market Returns: Study of Consumer Goods Companies Listed on the Indonesia Stock Exchange - Arie Pratania Putri; Jansen Hutagalung; Vivian Octavia; Carla Virginia (Soshum: Jurnal Sosial dan Humaniora, 2020)
Stocks have the highest risk between other investment instruments, but with the right analysis, the high risk is proportional to the high return that can be obtained. Stock return analysis can be done using a basic approach, namely fundamental analysis and technical analysis. This study aims to examine the effect of the individual stock price index, past stock price, debt to equity ratio (DER), and net profit margin (NPM) in consumer goods industry companies listed on the Indonesia Stock Exchange 2015-2018. This study uses multiple regression analysis models. The population of this study consisted of 60 companies, and the research sample consisted of 27 companies with 108 consumer goods industry companies listed on the Indonesia Stock Exchange 2015-2018 periods. The results showed that individual stock price index, past stock price, DER, and NPM simultaneously have a significant effect on stock return. Partially individual stock price index and past stock prices have a significant effect on stock return. In contrast, DER and NPM have no significant effect on stock return in consumer goods industry companies listed on the Indonesia Stock Exchange in the 2015-2018 periods.